Peroxisome Proliferator–Activated Receptor-α: A Pivotal Regulator of the Gastrointestinal Tract - Guo, Yue-Xin; Wang, Bo-Ya; Gao, Han; Hua, Rong-Xuan; Gao, Lei; He, Cheng-Wei; Wang, Ying; Xu, Jing-Dong (Frontiers in Molecular Biosciences, 2022)
Peroxisome proliferator–activated receptor (PPAR)-α is a ligand-activated transcription factor distributed in various tissues and cells. It regulates lipid metabolism and plays vital roles in the pathology of the cardiovascular system. However, its roles in the gastrointestinal tract (GIT) are relatively less known. In this review, after summarizing the expression profile of PPAR-α in the GIT, we analyzed its functions in the GIT, including physiological control of the lipid metabolism and pathologic mediation in the progress of inflammation. The mechanism of this regulation could be achieved via interactions with gut microbes and further impact the maintenance of body circadian rhythms and the secretion of nitric oxide. These are also targets of PPAR-α and are well-described in this review. In addition, we also highlighted the potential use of PPAR-α in treating GIT diseases and the inadequacy of clinical trials in this field.